Immunophenotypic characterization of canine malignant lymphoma: a retrospective study of cases diagnosed in Poland Lower Silesia, over the period 2011–2013. (23rd July 2014) - Pawlak, A.; Rapak, A.; Drynda, A.; Poradowski, D.; Zbyryt, I.; Dzimira, S.; Suchański, J.; Obmińska‐Mrukowicz, B.
Abstract: Lymphoma is the most frequently diagnosed cancer of the canine haematopoietic system. In this study, the flow cytometry and polymerase chain reaction (PCR) analysis were used to characterize a series of canine lymphomas in detail. The aim of this study was to determine the incidence of B‐ and T‐cell high‐grade lymphomas and their immunophenotypic characterization in Lower Silesia, Poland. The results show that the frequency of each type of lymphoma is 71% for B‐cell and 17% for T‐cell lymphomas. In two cases the PCR techniques confirmed the presence of simultaneous double gene rearrangements of the BCR and TCR receptors.